2015
DOI: 10.1186/s12863-015-0168-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive linkage map and QTL map for carcass traits in a cross between Giant Grey and New Zealand White rabbits

Abstract: BackgroundGenomic resources for the rabbit are still limited compared to many other livestock species. The genomic sequence as well as linkage maps have gaps that hamper their use in rabbit genome research. Therefore, the aims of this study were the improvement of existing linkage maps and the mapping of quantitative trait loci (QTL) for carcass and meat quality traits. The study was performed in a F2 population of an initial cross between Giant Grey (GG) and New Zealand White (NZW) rabbits. The population con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…The co-localization of 24 differentially expressed transcripts for MYB , bHLH , serine threonine kinases, RING zinc finger proteins with mQTL reported for zinc, zinc and phytate corroborated with the up regulated transcripts for phosphate transporters/ translocators in the landraces [ 59 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The co-localization of 24 differentially expressed transcripts for MYB , bHLH , serine threonine kinases, RING zinc finger proteins with mQTL reported for zinc, zinc and phytate corroborated with the up regulated transcripts for phosphate transporters/ translocators in the landraces [ 59 ].…”
Section: Discussionmentioning
confidence: 82%
“…The differentially expressed transcripts among the genotypes were mapped to the regions of metaQTLs (mQTLs) reported for iron and zinc content in rice for knowing their co-localization with QTL [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, we think that Bonferroni penalizes gene candidate studies too harshly, and the SNP was replicated in independent cohorts. Bonferroni is a useful multivariable test correction in several situations; however, the Bonferroni method is conservative and has low power (26, 27). It has been suggested that Bonferroni is a useful method in situations in which several subgroups of analysis have been tested, such as multi-stratification of the cohort (selection of women only, younger subjects only, etc.)…”
Section: Limitationsmentioning
confidence: 99%
“…The developments of microsatellite marker maps became available to estimate additive genetic effects of markers and were routinely used, for example, for Quantitative Locus (QTL) detection in most livestock species. This resulted in a breakthrough in genetic diversity analyses [20][21][22][23].…”
Section: Genomic Tools In Livestock Genetic Resources Conservationmentioning
confidence: 99%